Multicentre, randomised controlled trial of physiological-based cord clamping versus immediate cord clamping in infants with a congenital diaphragmatic hernia (PinC): statistical analysis plan - Horn-Oudshoorn, Emily J. J.; Vermeulen, Marijn J.; Knol, Ronny; Bout-Rebel, Rebekka; te Pas, Arjan B.; Hooper, Stuart B.; Otter, Suzan C. M. Cochius-den; Wijnen, Rene M. H.; Crossley, Kelly J.; Rafat, Neysan; Schaible, Thomas; de Boode, Willem P.; et al. (Trials, 2024)
Infants born with congenital diaphragmatic hernia (CDH) are at high risk of respiratory insufficiency and pulmonary hypertension. Routine practice includes immediate clamping of the umbilical cord and endotracheal intubation. Experimental animal studies suggest that clamping the umbilical cord guided by physiological changes and after the lungs have been aerated, named physiological-based cord clamping (PBCC), could enhance the fetal-to-neonatal transition in CDH. We describe the statistical analysis plan for the clinical trial evaluating the effects of PBCC versus immediate cord clamping on pulmonary hypertension in infants with CDH (PinC trial). The PinC trial is a multicentre, randomised controlled trial in infants with isolated left-sided CDH, born ≥ 35.0 weeks of gestation. The primary outcome is the incidence of pulmonary hypertension in the first 24 h after birth. Maternal outcomes include estimated maternal blood loss. Neonatal secondary outcomes include mortality before discharge, extracorporeal membrane oxygenation therapy, and number of days of mechanical ventilation. Infants are 1:1 randomised to either PBCC or immediate cord clamping using variable random permutated block sizes (4-8), stratified by treatment centre and estimated severity of pulmonary hypoplasia (i.e. mild/moderate/severe). At least 140 infants are needed to detect a relative reduction in pulmonary hypertension by one third, with 80% power and 0.05 significance level. A chi-square test will be used to evaluate the hypothesis that PBCC decreases the occurrence of pulmonary hypertension. This plan is written and submitted without knowledge of the collected data. The trial has been ethically approved. ClinicalTrials.gov NCT04373902 (registered April 2020).
Gesehen am 09.01.2025